Effect of Cilostazol on Incident Dementia in Elderly Men and Women with Ischemic Heart Disease - Kim, Mi Young; Noh, Yoojin; Son, Sang Joon; Shin, Sooyoung; Paik, Hee Young; Lee, Sukhyang; Jung, Yi Sook (Journal of Alzheimer's Disease, 2018)
Background: Ischemic heart disease (IHD) is associated with cognitive decline and may contribute to an increased risk of dementia. Objective: The goal of the present study was to investigate whether cilostazol use is associated with a lower risk of incident dementia in Asian patients with IHD, and whether these effects differed based on sex. Methods: This retrospective cohort study was performed using the Korean National Insurance Claim Data of the Health Insurance Review and Assessment Service; the duration of the study was from January 1, 2007 to December 31, 2015. The study group comprised 66,225 patients with IHD, aged >65 years, who had received cilostazol. Age- and sex-matched IHD patients without cilostazol exposure were selected as the control group. The risk of dementia was compared between the cilostazol and control groups. Results: Compared to the control group, total cilostazol users had a marginally significant lower risk of incident dementia. After stratification by sex, the reducing effect of cilostazol on incident dementia was significant in female participants, but not in male participants. Female patients who had cilostazol for over 2 years showed a clinically meaningful preventive effect (HR, 0.85; 95% CI, 0.82-0.88). Conclusions: This study suggested that cilostazol treatment may reduce the risk of incident dementia in Korean patients with IHD. Its beneficial effect was remarkably significant in female patients who received cilostazol for over a 2-year period.
Keywords: Aged; Aged, 80 and over; Cilostazol; Cohort Studies; Dementia; Female; Humans; Male; Myocardial Ischemia; Nootropic Agents; Phosphodiesterase 3 Inhibitors; Platelet Aggregation Inhibitors; Risk Factors; Sex Factors; Cilostazol; dementia; ischemic heart disease; sex difference